2001
DOI: 10.1038/sj.onc.1204582
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical differences between SUDHL-1 and KARPAS 299 cells derived from t(2;5)-positive anaplastic large cell lymphoma are responsible for the different sensitivity to the antiproliferative effect of p27Kip1

Abstract: An inverse correlation between p27 Kip1 expression and proliferation has been recently established in tissues derived from human lymphomas. The nucleophosminanaplastic lymphoma kinase (NPM ± ALK)/phospholipase C-g (PLCg) complex also appears to play an important role in cell proliferation and malignant transformation of anaplastic large cell lymphoma (ALCL). In this study, we report that SUDHL-1 and KARPAS 299 ALCL-derived cell lines present di erent sensitivity to the antiproliferative e ect of recombinant ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…[17][18][19] For the first time, we showed that adenovirus-mediated p27 Kip1 expression was able to induce in vitro apoptosis in SUDHL-1 cells derived from t(2:5)-ALCL. 20, 21 We also demonstrated that the effects of adenovirus-mediated p27 Kip1 expression were cell dependent and differed from the effects of adenovirus-mediated p53 expression in SUDHL-1 cells. 20 22 On the contrary, cells derived from HD were resistant to apoptosis induced by the same recombinant adenoviruses.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 74%
See 3 more Smart Citations
“…[17][18][19] For the first time, we showed that adenovirus-mediated p27 Kip1 expression was able to induce in vitro apoptosis in SUDHL-1 cells derived from t(2:5)-ALCL. 20, 21 We also demonstrated that the effects of adenovirus-mediated p27 Kip1 expression were cell dependent and differed from the effects of adenovirus-mediated p53 expression in SUDHL-1 cells. 20 22 On the contrary, cells derived from HD were resistant to apoptosis induced by the same recombinant adenoviruses.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 74%
“…20, 21 We also demonstrated that the effects of adenovirus-mediated p27 Kip1 expression were cell dependent and differed from the effects of adenovirus-mediated p53 expression in SUDHL-1 cells. 20 22 On the contrary, cells derived from HD were resistant to apoptosis induced by the same recombinant adenoviruses. 22 The difference in the level of apoptosis was correlated with the level of phosphorylation of the retinoblastoma (Rb) protein in the cell lines tested.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 74%
See 2 more Smart Citations
“…Notably, some variability in the cellular response to TrkAi was observed among the different lymphoma cell lines. This variability could be explained, at least in part, by the intrinsic biochemical differences among these cell lines (Turturro et al ., 2001). Importantly, the cellular and biochemical effects of selective inhibition of TrkA by TrkAi were consistent when specific downregulation of TrkA was achieved by using siRNA.…”
Section: Discussionmentioning
confidence: 99%